Literary analysis of covenant themes in the book of Malachi - Boloje, Blessing Onoriode (Old Testament essays, 2015)
The category of covenant is considered to be the dominant and cohesive idea in the theology of the OT. It is the means through which Israel conceptualise its relation with Yahweh. Although the term "covenant" is variously and even contradictorily defined, its applicability to Israel's conceptualisation of its relationship with Yahweh is pervasive and well-known. The covenant relationship between Israel and Yahweh is considered to be its constitution, its vocation, and its salvation. From a theological view point, the essential components of Malachi's oracles are the person-hood of Yahweh - the God of Israel, Yahweh's covenant relationship with Israel, and the all-pervasive message of unreserved and enthusiastic personal response of Israel to the truth assertions of the prophetic voice. This article thus demonstrates the significance of covenant as the central and cohesive theological motif connecting and coordinatingseveral themes present in the book of Malachi as well as illuminating its message. In Malachi, one observes that certain religious fundamentals were compromised. In order to deal with the indifference and its adverse consequences in the gradual decline towards an unstructured existence and to hold together a society that upholds values and maintains an ancient faith, Malachi was skill-full and creative in his employment of the covenant theme to the advantage of his ministerial context. The article presents precise background and historical information about the book of Malachi that are crucial to an understanding of its theme and message, the book's literary style, theme and structure, examines the various covenant themes and then concludes by synthesising these themes with the overall message of the book's context.,